Organizational, environmental, and sustainability of inputs to the implementation of a smoke-free area policy: A path analysis of Makassar's health facilities - Ismaniar, Nur Inayah; Wahyudin , Wahyudin; Paratama, Faradillah (Svāsthya: Trends in General Medicine and Public Health, 2025)
The implementation of smoke-free policies in healthcare facilities represents a critical public health strategy; however, maintaining sustainable compliance remains a challenge globally. While healthcare institutions are expected to exemplify tobacco control measures, the effectiveness of smoke-free policies depends on multiple factors at the institutional and governmental levels. This study aimed to examine the influence of organizational, environmental, and sustainability factors on input indicators for smoke-free area policy implementation in healthcare facilities in Makassar, Indonesia. A quantitative correlational study was conducted across seven healthcare facilities that provide inpatient services. Using random cluster sampling, 232 healthcare workers were selected from a population of 736. Path analysis was employed to evaluate causal relationships between independent variables (organizational, environmental, and sustainability factors) and dependent variables (input indicators, including written policies, monitoring personnel, and promotional media). Data were collected through validated questionnaires and analyzed via structural equation modeling. Path analysis revealed that sustainability factors significantly influenced input indicators, particularly written policies (t statistic = 2.592, p<0.05, β=0.194). Key sustainability components, including funding stability, partnerships, organizational capacity, program evaluation, adaptation, and strategic planning, have demonstrated positive effects on policy implementation. Organizational and environmental factors had no significant impact on the input indicators. Sustainability factors emerged as crucial determinants for the successful implementation of smoke-free policies in healthcare facilities in Makassar city. Future research should investigate the barriers to policy implementation and explore additional input indicators to increase the effectiveness of smoke-free policies.